Screening of the human tumor necrosis factor (TNF) gene and its receptor 1 (TNFR1) gene for DNA alterations and the subsequent investigation of these and an IL12p40 polymorphism for an association with paediatric tuberculosis - Lampel, Netanya (Department of Paediatrics and Child Health, 2014)
Includes bibliographical references (leaves 85-96).